Leakage in nasal high‐frequency oscillatory ventilation improves carbon dioxide clearance—A bench study. Issue 3 (15th August 2016) - Klotz, Daniel; Schaefer, Christoph; Stavropoulou, Dimitra; Fuchs, Hans; Schumann, Stefan
Summary: Objective: Nasal high frequency oscillatory ventilation (nHFOV) is a promising mode of non‐invasive neonatal respiratory support. To combine the effects of nasal continuous positive airway pressure (nCPAP) and high frequency oscillatory ventilation, an oscillatory pressure waveform is superposed to a nCPAP via a nasal or nasopharyngeal interface. nHFOV has been described to facilitate carbon dioxide (CO2 ) elimination compared to nCPAP. The influence of unintended leakage on CO2 elimination has not been investigated in nHFOV before. We explored the effects of oral leakage on CO2 elimination during nHFOV in a physical model of the neonatal respiratory system. Methods: A neonatal ventilator was connected to an airway‐ and lung model using binasal prongs as interface. The model comprised a continuous CO2 influx. Alveolar CO2 partial pressure was continuously measured. Gas flow rates and pressures were measured simultaneously at the prongs, pharynx, lung, and at the leakage. Effects of combined nasopharyngeal leakage (0, 5, or 10 L/min) on CO2 elimination, gas flow rate and pressure were determined at various ventilation frequencies (6, 8, 10, and 12 Hz) and amplitudes (10%, 20%, and 30% of maximum ventilator performance) at a mean airway pressure of 10 cmH2 O. Results: nHFOV with moderate leakage was more effective in CO2 elimination than without leakage ( P < 0.001) for all tested amplitudes and frequencies. Maximum leakage resulted in highly variable, partly ineffective CO2 elimination. Conclusions: A moderate oral leakage rather improves than impairs gas exchange during non‐invasive ventilatory support with nHFOV.Pediatr Pulmonol. 2017;52:367–372. © 2016 Wiley Periodicals, Inc.